The effect of chromium and cobalt segregation at dislocations on nickel-based superalloys. (1st March 2018) - Kontis, Paraskevas; Li, Zhuangming; Collins, David M.; Cormier, Jonathan; Raabe, Dierk; Gault, Baptiste
Abstract: The segregation of solutes at dislocations in a polycrystalline and a single crystal nickel-based superalloy is studied. Our observations confirm the often assumed but yet unproven diffusion along dislocations via pipe diffusion. Direct observation and quantitative, near-atomic scale segregation of chromium and cobalt at dislocations within γ' precipitates and at interfacial dislocations leading to the partial or complete dissolution of γ' precipitates at elevated temperatures is presented. Our results allow us to elucidate the physical mechanism by which pipe diffusion initiates the undesirable dissolution of γ' precipitates. Graphical abstract: